Optimal Domain and Integral Extension of Operators - I. Gohberg, D. Alpay, J. Arazy, A. Atzmon, J. A. Ball, A. Ben-Artzi, H. Bercovici, A. Böttcher, K. Clancey, L. A. Coburn, R. E. Curto, K. R. Davidson, R. G. Douglas, A. Dijksma (Springer, 2017)
406 p.